Head Impact Exposure Sustained by Football Players on Days of Diagnosed Concussion - Beckwith, Jonathan G. (2013)
PURPOSE: This study compares the frequency and severity of head impacts sustained by football players on days with and without diagnosed concussion and to identify the sensitivity and specificity of single impact severity measures to diagnosed injury. METHODS: 1,208 players from eight collegiate and six high school football teams wore instrumented helmets to measure head impacts during all team sessions, of which 95 players were diagnosed with concussion. Eight players sustained two injuries and one three, providing 105 injury cases. Measures of head kinematics (peak linear and rotational acceleration, Gadd Severity Index (GSI), Head Injury Criteria (HIC(15)), change in head velocity (Δv)) and the number of head impacts sustained by individual players were compared between days with and without diagnosed concussion. Receiver operator characteristic curves were generated to evaluate the sensitivity and specificity of each kinematic measure to diagnosed concussion using only those impacts that directly preceded diagnosis. RESULTS: Players sustained a higher frequency of impacts and impacts with more severe kinematic properties on days of diagnosed concussion than on days without diagnosed concussion. Forty-five injury cases were immediately diagnosed following head impact. For these cases, peak linear acceleration and HIC(15) were most sensitive to immediately diagnosed concussion (AUC = 0.983). Peak rotational acceleration was less sensitive to diagnosed injury than all other kinematic measures (p = 0.01) which are derived from linear acceleration (peak linear, HIC(15), GSI, and Δv). CONCLUSIONS: Players sustain more impacts and impacts of higher severity on days of diagnosed concussion than on days without diagnosed concussion. Additionally, of historical measures of impact severity, those associated with peak linear acceleration are the best predictors of immediately diagnosed concussion.